KEMAMPUAN PEMAHAMAN KONSEP PADA PEMBELAJARAN MATEMATIKA BERORIENTASI REACT DAN STEM - Elfi Rahmadhani; Septia Wahyuni; Lola Mandasari (AKSIOMA: Jurnal Program Studi Pendidikan Matematika, 2021)
This research is a development research with the aim to develop the learning of mathematics oriented REACT and STEM to see the understanding of mathematical concepts of students. The learning tools developed are lesson plans, strudent worksheets and sudent books. The development model used is ADDIE (Analysis, Design, Development, Implementation and Evaluation). The material used in the learning device developed is the Bangun Datar material with the research subject being class VII students of SMP N 1 Takengon which consists of 28 students. The instruments used in this study were RPP validation sheets, worksheets, modules, concept understanding tests, and teacher and student response questionnaires to the developed tools. Analysis of the data used is the analysis of validity, practicality, and effectiveness. The results obtained are learning tools are included in the valid category, based on the results of validation by validators of mathematics education experts, learning model experts and learning media experts. The device is categorized as practical to use based on 1) the results of observations of the teacher's ability to carry out the learning process using the learning tools developed are classified as good, 2) the teacher's response to the device is very good, and 3) the student response is very good to the device. REACT and STEM oriented learning tools are also effectively used to see students' conceptual understanding abilities which show that the average score of students is more than the KKM set by the school, which is 83.60 > 70